2019
DOI: 10.1016/j.jbmt.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive non-surgical management of plantar fasciitis: A systematic review

Abstract: Background: Minimally invasive non-surgical techniques have been widely used worldwide to treat musculoskeletal injuries. Of these techniques, injectable pharmaceutical agents are the most commonly employed treatments, with corticosteroids being the most widely used drugs. The aim of this article is to review current scientific evidence as well as the effectiveness of minimally invasive non-surgical techniques, either alone or combined, for the treatment of plantar fasciitis. Methods: This systematic review wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Recent systematic reviews have also suggested similar outcomes with ESWT and CSI and ACP injection therapies for PHP [8,68,69]. This suggests these invasive injection therapies may be unnecessary if ESWT is available as a treatment option as it is associated with less side effects and a better safety profile [70][71][72].…”
Section: Discussionmentioning
confidence: 90%
“…Recent systematic reviews have also suggested similar outcomes with ESWT and CSI and ACP injection therapies for PHP [8,68,69]. This suggests these invasive injection therapies may be unnecessary if ESWT is available as a treatment option as it is associated with less side effects and a better safety profile [70][71][72].…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, key information errors were found in two review protocols, confusing the exposure and outcome subgroup leading to a lack of clarity [24,27]. Other errors were discovered including the fact that protocols did not provide the details of the search strategy, despite the fact that the published review [34] stated explicitly that the detailed search strategy could be found in the protocol.…”
Section: The Results Of Comparisonmentioning
confidence: 99%
“…However, conservative treatment requires a long period of absolute bed rest, which often affects the normal life and work of soldiers. Consequently, the concept of minimally invasive treatment is put forward and widely adopted due to its convenience and accurate effect [ 68 ].…”
Section: Effects Of Prp On Military Drill Injurymentioning
confidence: 99%